Genetic diversity and population structure of Peronosclerospora sorghi isolates of Sorghum in Uganda - Kumi, Frank; Agbahoungba, Symphorien; Badji, Arfang; Mwila, Natasha; Ibanda, Angele; Anokye, Michael; Odong, Thomas; Wasswa, Peter; Ochwo- Ssemakula, Mildred; Tusiime, Geoffrey; Biruma, Moses; Kassim, Sadik; et al. (International Journal of Environment, Agriculture and Biotechnology (IJEAB), 2018)
Sorghum is the third most important staple cereal crop in Uganda after maize and millet. Downy mildew disease is one of the most devastating fungal diseases which limits the production and productivity of the crop. The disease is caused by an obligate fungus, Peronosclerospora sorghi (Weston & Uppal) with varying symptoms. Information on the genetic diversity and population structure of P.sorghi in sorghum is imperative for the screening and selection for resistant genotypes and further monitoring possible mutant(s) of the pathogen. Isolates of P. sorghi infecting sorghum are difficult to discriminate when morphological descriptors are used. The use of molecular markers is efficient, and reliably precise for characterizing P. sorghi isolates. This study was undertaken to assess the level of genetic diversity and population structure that exist in P. sorghi isolates in Uganda.
Keywords: AMOVA; Genetic diversity Index; ISSR; Mantel test; RAM; Shannon Information Index